2014
DOI: 10.1111/clr.12507
|View full text |Cite
|
Sign up to set email alerts
|

Improved osseointegration and interlocking capacity with dual acid‐treated implants: a rabbit study

Abstract: Aim: To investigate how osseointegration is affected by different nano-and microstructures. The hypothesis was that the surface structure created by dual acid treatment (AT-1), applied on a reduced topography, might achieve equivalent biomechanical performance as a rougher surface treated with hydrofluoric acid (HF). Materials and methods:In a preclinical rabbit study, three groups (I, II, and III) comprised of test and control implants were inserted in 30 rabbits. The microstructures of the test implants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 30 publications
(54 reference statements)
2
22
0
Order By: Relevance
“…33 It has been reported by Halldin et al that dual acid-etched implants with a reduced microtopography in height deviation, presented equivalent osseointegration compared to the commercially available fluoride-treated implants in a biomechanical investigation using rabbits. 34 Thus, it can be speculated that parameters other than the arithmetic average height deviation was altered in a manner that it stimulated osteogenesis for surface L.…”
Section: Discussionmentioning
confidence: 99%
“…33 It has been reported by Halldin et al that dual acid-etched implants with a reduced microtopography in height deviation, presented equivalent osseointegration compared to the commercially available fluoride-treated implants in a biomechanical investigation using rabbits. 34 Thus, it can be speculated that parameters other than the arithmetic average height deviation was altered in a manner that it stimulated osteogenesis for surface L.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the topography and chemistry of the surface properties can control the quantity and quality of adhered cells to the implant (Rosales-Leal et al, 2010, Logan and Brett, 2013). It has been reported that optimal surface roughness can lead to effective osseointegration (Halldin et al, 2014). This effect was due to increased osteoblast proliferation, differentiation and matrix protein production, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The coordinates (x, y and z) from a representative patch of each of the three different (A, B and C) surfaces used in the study by Halldin et al [ 27 ] were extracted from interferometry measurements. Group A were blasted with coarse titanium particles thereafter treated in oxalic acid and hydrofluoric acid sequentially (CB-AT-I).…”
Section: Methodsmentioning
confidence: 99%
“…Group C implants were blasted with coarse titanium particles thereafter treated in hydrofluoric acid (CB-HF). The representative patches were selected to have surface average height values (S a ) close to the mean S a values of the implant in Halldin et al [ 27 ]. The x, y and z coordinates were imported into MATLAB (MATLAB 2013b, Mathworks Inc., USA) to calculate the average height values (S a [μm]), root-mean-square (S q [μm]), skewness (S sk [μm/μm]) and the root-mean-square of the surface slope (S dq [μm/μm]) of the selected patches [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation